Specificity of psychological readiness for changes and personality’s maturity of the employees of the state criminal and executive service (Law and Safety, 2018)
The work focuses on the study of psychological readiness for changes and personality’s maturity among the employees of the State Criminal and Executive Service of Ukraine. It is shown that readiness for changes in the reforming conditions is a psychological condition for successful professional activity and personal self-realization of the staff of the criminal and executive service. The content of the concepts of “psychological readiness” and “psychological readiness for changes” is revealed; the purposefulness of the study of personality’s maturity as one of the factors of psychological readiness for changes is substantiated. The purpose of the study was to identify the features of the functioning of psychological readiness for changes in the context of personal maturity of the employees of the State Criminal and Executive Service of Ukraine.The PCRS (Personal Changes Readiness Survey) method created by A. Rolnic, S. Heather, M. Gold, C. Hull (translation and adaptation by N. A. Bazhanova and G. L. Bardier) and the questionnaire of personal maturity (O. S. Shtepa) were applied to solve empirical problems. The subjects were employees of the State Criminal and Executive Service of Ukraine, who were divided into groups according to the level of psychological readiness for changes. The first group consisted of subjects with a high level of readiness for changes, the second – with a low level.The scientific novelty of the research is determined by the fact that the author established, for the first time, the features of psychological readiness for changes of the employees of the Criminal and Executive Service of Ukraine in the context of personal maturity. It was found out that the employees of the Criminal and Executive Service with a high level of psychological readiness for changes are distinguished by the greater severity of its components, such as responsibility, depth of experience, tolerance, autonomy, self-acceptance and synergy. It was proved that the groups of the employees of the Criminal and Executive Service with different levels of psychological readiness for changes show differences in the structure of interrelationships between the components of psychological readiness for changes and the components of personal maturity. In both groups, the growth of personality maturity is accompanied by a facilitation of psychological readiness for changes. At the same time, there were almost twice as many interconnections between these phenomena in the group with high level of psychological readiness for changes, which indicated an active interaction between them in this group, in contrast to the low-level group, where this interaction was rather limited. The obtained results allow us to conclude that the subjects with different levels of psychological readiness for changes demonstrate differences both in the indicators of personal maturity and in the structure of interrelations between the components of psychological readiness for changes and personal maturity. Less distinct manifestation of a number of components of psychological readiness for changes and a certain deficiency of its interaction with personality maturity can hinder both the successful professional activity of low-level group and their optimal functioning in the personality’s sense. The results obtained in the study can be used to develop programs for psychological support of the professional activities of the staff of the Criminal and Executive Service at the stage of its reformation.
Keywords: personality’s maturity; employees of the Criminal and Executive Service; professional activity; psychological readiness; psychological readiness for changes